Colloquies - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974, 1997)
Erasmus' Familiar Colloquies grew from a small collection of phrases, sentences, and snatches of dialogue written in Paris around 1497 to help his private pupils improve their command of Latin.